Seafood Trade Routes for Lobster Obscure Teleconnected Vulnerabilities - Stoll, Joshua S.; Crona, Beatrice I.; Fabinyi, Michael; Farr, Emily R. (Frontiers in Marine Science, 2018)
Reliance on international seafood markets leaves small-scale fishers and fishing economies vulnerable to distant disturbances that can negatively affect market prices and trigger social, economic, and environmental crises at local levels. This paper examines the role of seafood trade routes and re-exports in masking such market linkages. We employ a network approach to map the global trade routes of lobster (Homarus spp.) from small-scale producers in North America to terminal markets and evaluate the extent to which intermediary nations act to obscure producer-market relationships. In taking this approach, we provide a method for systematically measuring 'teleconnectivity' created through seafood trade routes, and thus making explicit vulnerabilities to small-scale fisheries from this teleconnectivity. Our empirical analysis shows that the perceived trade diversification of lobster producers is masking increased dependencies on a reduced number of end-markets, particularly in Asia. These results suggest, paradoxically, that the apparent diversification of trade partnerships may actually amplify, rather than reduce, the vulnerabilities of small-scale fishers associated with international trade by making risk harder to identify and anticipate. We discuss our results in the context of local fisheries and global seafood trade and describe key impediments to being able to monitor market dependencies and exposure to potential vulnerabilities.